2015
DOI: 10.7287/peerj.preprints.1066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trace element contamination severity of coastal waters: A first bioassessment at the scale of the whole Mediterranean Sea

Abstract: Human activities generate large volumes of waste that supply marine coastal environments in pathogens, organic matter, nutrients and toxicants. Among the wide range of toxicants are trace elements. Since the latter are toxic for aquatic organisms from threshold levels and as they are therefore likely to cause multiple damage to the population, the community and the ecosystem levels, their environmental occurrence has to be accurately monitored in order to guarantee appropriate environmental management of coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…4). The metal pollution index values of our study were found to be higher than Richeir and Gobert [42] and Richer et al [43] studies.…”
Section: Metal Pollution Indexcontrasting
confidence: 83%
“…4). The metal pollution index values of our study were found to be higher than Richeir and Gobert [42] and Richer et al [43] studies.…”
Section: Metal Pollution Indexcontrasting
confidence: 83%